Problematika Kompetensi Literasi Peserta Didik dalam Pembelajaran yang Memanfaatkan Ragam Perangkat Digital - Maulida, Annisa Nurwulan; Umaya, Nazla Maharani (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
The development of the times in the era of technology into digital devices plays an important role in fostering the spirit of creativity of every human being. The use of digital devices is inseparable in the field of education which provides convenience or creates problems in less wise use. Problems are created due to excessive use of digital devices, namely affecting the literacy competence of each individual, especially students in the field of education. That way the problems that will be discussed in the article are problems in the field that affect the decline in literacy competence in students due to the unwise use of digital devices. This research has objectives that the author wants to achieve, namely 1) to make readers aware of the influence of using digital devices, and 2) to strategize effective learning tools so that students are more interested in reading book literacy. This article research uses a type of qualitative research that is a literature study with the results of reviewing the problems experienced in the field and then strengthened by previous studies that are relevant to the title of the article.